CFD analysis on flow through nozzle of conical type and truncated conical plug type. (2023) - Gayathri, N.; Senthilkumar, P.; Dineshkumar, K.; Purusothaman, M.; Sriharan, B.
Abstract: Conical type nozzle and truncated conical plug type nozzles have been recently developed rocket nozzles appropriate as elevation compensating nozzles. This research work focuses on the analysis of flow through nozzle types of conical plug type and truncated plug type nozzles. It is statistically simulated and validated with the values of experimental data. Also, it is aimed to relate the performance while a base bleed is being introduced. Two-dimensional axisymmetric model is being considered for statistical analysis. Reynolds Averaged Navier Stokes (RANS) equations are resolved with two-equation shear stress transport k-ɛ turbulence kind model. Along with the flow patterns, the wall pressure of conical plug type nozzle and base pressures of truncated plug type nozzle were evaluated at a range of pressure ratios of the nozzle. Mathematical models about these in two-equation flow have been solved using CFD software ANSYS fluent. Three-dimensional simulation has also been performed to explore the flow in the turbulent RANS and models in two-equation flow. Suitable boundary conditions are adopted during the analysis to predict the flow characteristics. Form the results obtained, it is understood that the flow separation region prolongs with the increase in nozzle pressure ratio for 40% truncated conical plug type nozzle. It is also observed that, the 40% conical plug type contributed to a higher thrust, flow velocity and Mach number. Increase in nozzle pressure ratio increases the length of flow pattern for a truncated plug type nozzle.